Gangguan Fungsi Bahasa Meningkatkan Risiko Kualitas Hidup Buruk pada Lansia - Piustan, Mas Eaufrat; Turana, Yuda; Handajani, Yvonne Suzy; Kristian, Kevin (PERDOSNI, 2025)
Introduction: The quality of life of the elderly requires attention. Language function is closely related to identifying individuals who are vulnerable to a decline in quality of life. Aim: This study aims to examine the relationship between sociodemographic factors, language function, social engagement, and frailty with elderly’s quality of life. Methods: This study employed a cross-sectional method with 100 respondents aged ≥60 years. Quality of life was measured using the WHOQOL-BREF, language function was assessed using the CERAD Verbal Fluency Test, social engagement was evaluated using the Social Disengagement Index, frailty was measured using the Fried Frailty Index, and sociodemographic factors were assessed through interviews using validated instruments. Results: Chi-square analysis showed a significant relationship between language function and the psychological, social, and environmental domains (p<0.05). Gender was only significantly associated with the environmental domain. Frailty was associated with psychological, social, overall quality of life, and health satisfaction. Multiple logistic regression analysis shows that impaired language function is a risk factor for impairments in the psychological (OR=3.335; 95%CI=1.376-8.082), social (OR=3.473; 95%CI=1.376-8.763), and environmental domain (OR=4.649; 95%CI=1.057-20.442). Frailty was identified as risk factor for impairments in psychological domain (OR=3.274; 95%CI=1.069-10.022) and health satisfaction (OR=3.378; 95%CI=1.105-10.328). Being female served as protective factor against impairments in the environmental domain (OR=0.159; 95%CI=0.036-0.694). Discussion: Impaired language function increase the risk of psychological, social, and environmental impairments. Being female serves as protective factor against environmental domain impairment. Frailty increases the risk of psychological impairments and poor health satisfaction. Keywords: Age, elderly, frailty, language, quality of life